PSI-5 Biweekly administration of recombinant bovine somatotropin during the first trimester of pregnancy failed to alter uterine hemodynamics in suckled beef cows. (7th December 2018) - Sanford, C; Owen, M; McCarty, K; Canal, L; Fontes, P; Oosthuizen, N; Ciriaco, F; Henry, D; Schulmeister, T; DiLorenzo, N; Lemley, C; Lamb, G
Abstract: The objective was to examine the effects of recombinant bovine somatotropin (bST) administration on uterine hemodynamics in suckled cows during the first trimester of gestation. Crossbred beef cows (n = 150) were stratified by breed, days postpartum, parity, estrous cyclicity status, and BCS before being assigned to either bi-weekly injections of bST (BST; 500 mg/14 d) at fixed-timed artificial insemination (TAI; d 0) until d 97 or no bST (CTL). Blood samples were collected biweekly until d 97 for analysis of plasma concentrations of IGF-1. Cow BW and BCS was recorded on d -10, 0, 13, 27, 41, 55, 69, 83, 97, 173, and 233. Pregnancy was assessed via transrectal ultrasonography on d 41 and 173. A subset of pregnant cows (BST, n = 24; CTL, n = 28) were selected for assessment of uterine arterial BF, pulsatility index, and resistance index of the uterine arteries ipsilateral and contralateral to the conceptus via Doppler ultrasonography on d 97 and 233. Data were analyzed using PROC MIXED of SAS with repeated measures. The model included the fixed effects of treatment, parity and d, and the random effect of cow (treatment parity). No differences (P < 0.10)were detected for BW or BCS; however, plasma concentrations of IGF-1 were greater (P < 0.001) in BST-treated cows. No differences (P > 0.10) were detected for Doppler ultrasonography parameters. A treatment × d interaction (P = 0.007) was detected for maximal systolic velocity (Vmax), where no differences were observed on d 97; however, on d 233, Vmax was greater (P < 0.001) for BST-treated cows. Mean heart girth diameter, crown-to-rump length, and calf birth weight did not differ (P > 0.10). Bi-weekly administration of bST increased plasma concentrations of IGF-1 but failed to alter uterine hemodynamics or calf size at birth.